Addressing the major information technology challenges of electronic textbooks - Lee, Jasmine Hee Jeong; Yau, Alvin Kok-Lim * (Taylor & Francis, 2015)
Electronic textbooks (e-Textbooks) are digitized forms of textbooks which are envisioned to replace existing paper-based textbooks. After intensive literature review, together with interview results, our study has figured out four major IT-based challenges associated with e-Textbooks in its pursuit to replace the traditional textbooks, namely standardizing format of content, improving service reliability, improving quality and accuracy of content, and improving readability. This paper also provides an extensive review on how these challenges have been approached using existing e-Textbook solutions, such as N-Screen services, cloud computing, open market place, P2P between devices and HTML5. For each solution, we develop a usage scenario in which users apply the aforementioned technologies to interact with e-Textbooks and share contents among themselves. This article aims to provide a strong foundation for further investigations into the development and distribution of e-Textbooks for eventual successful adoption of e-Textbooks in school education.